Infantile myofibromatosis: Excellent prognosis but also rare fatal progressive disease. Treatment results of five Cooperative Weichteilsarkom Studiengruppe (CWS) trials and one registry. Issue 3 (11th October 2021) - Sparber‐Sauer, Monika; Vokuhl, Christian; Seitz, Guido; Sorg, Benjamin; Tobias, Möllers; von Kalle, Thekla; Münter, Marc; Bielack, Stefan S.; Ladenstein, Ruth; Ljungman, Gustaf; Niggli, Felix; Frühwald, Michael; et al.
Abstract: Background: Infantile myofibromatosis (IM) is a rare benign soft tissue tumor and often a self‐limiting disease but rarely includes life‐threatening complications. Little is known about optimal treatment of primary localized (LD) and multifocal disease (MFD). Methods: Treatment and outcome of 95 children with IM registered within five Cooperative Weichteilsarkom Studiengruppe (CWS) trials and one registry (1981–2016) were evaluated. Results: LD was diagnosed in 71 patients at a median age of 0.4 years (range 0.0–17.7). MFD was present in 24 patients. The mainstay of treatment was watch‐and‐wait strategy (w&w) after initial biopsy or resection. Low‐dose chemotherapy (CHT) was administered to 16/71 (23%) patients with LD and eight of 24 (33%) patients with MFD, imatinib was added in two. A delayed resection was possible in eight of 71 (11%) and five of 24 (21%) patients with LD and MFD, respectively. Overall, patients were alive in complete remission ( n = 77) and partial remission ( n = 10) at a median follow‐up time of 3.4 years after diagnosis (range 0.01–19.4); no data available ( n = 5). Three patients died of progressive disease (PD) despite CHT. Gender, tumor size, and location correlated with a favorable event‐free survival (EFS) in patients with LD. The 5‐year EFS and overall survival of patients with LD were 73% (±12, confidence interval [CI] 95%) and 95% (±6, CI 95%), respectively; for MFD 51% (±22, CI 95%) and 95% (±10, CI 95%). Conclusion: Prognosis is excellent in patients with LD and MFD. Targeted treatment needs to be evaluated for rare fatal PD.